2016
DOI: 10.1007/s12015-016-9703-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Attenuate the Adverse Effects of Immunosuppressive Drugs on Distinct T Cell Subopulations

Abstract: Immunosuppressive drugs are widely used to treat undesirable immune reaction, however their clinical use is often limited by harmful side effects. The combined application of immunosuppressive agents with mesenchymal stem cells (MSCs) offers a promising alternative approach that enables the reduction of immunosuppressive agent doses and simultaneously maintains or improves the outcome of therapy. The present study aimed to determinate the effects of immunosuppressants on individual T cell subpopulations and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…MSCs, which are involved in the differentiation of different T cell subsets, can also regulate T cell functions, such as the secretion of type 1/type 2 cytokines. Recent works showed that MSCs inhibit TNF-a, IFN-g, IL-2, IL-6, and IL-17 expression in CD4 + and CD8 + T cells, whereas they upregulate IL-4, IL-10, and TGF-b expression in CD4 + T cells (18,51,52). IL-10 has been shown to be one of the primary mediators by which CD4 + CD25 + Tregs mitigate the severity of GVHD, and donor as well as host B cellderived IL-10 contributes to the suppression of GVHD (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs, which are involved in the differentiation of different T cell subsets, can also regulate T cell functions, such as the secretion of type 1/type 2 cytokines. Recent works showed that MSCs inhibit TNF-a, IFN-g, IL-2, IL-6, and IL-17 expression in CD4 + and CD8 + T cells, whereas they upregulate IL-4, IL-10, and TGF-b expression in CD4 + T cells (18,51,52). IL-10 has been shown to be one of the primary mediators by which CD4 + CD25 + Tregs mitigate the severity of GVHD, and donor as well as host B cellderived IL-10 contributes to the suppression of GVHD (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…in a rat model of liver transplantation, Xu et al (16) found that the proportion of Treg cells in peripheral blood mononuclear cells in the rapamycin treatment group was higher compared with the group treated with tacrolimus. Hajkova et al (17) reported that the inhibitory effects of BM-MScs on cd4 + rorγt + Th17 were significantly reduced after treatment with tacrolimus. The addition of rapamycin significantly reduced the expression of il-17, whereas rapamycin significantly increased the expression of Foxp3 in the co-culture of MScs and cd4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MSCs achieved direct immune regulation after the contact with effector T cells by releasing NO or Fas/FasL pathway, which induced apoptosis [32]. MSCs could directly secrete anti-inflammatory cytokines such as transforming growth factor (TGF-β), interleukin 6 (IL-6), interleukin 10 (IL-10), indolamine 2,3-dioxygenase (IDO), vascular endothelial growth factor (VEGF), intercellular adhesion molecule (ICAM), prostaglandin E2 (PGE2) and expression inhibitory co-stimulatory molecules such as programmed death ligand-1 (PD-L1) to realize the function of immunoregulation [40][41][42]. Further, it has been reported that Th1 and Th17 cells completed the repolarization process attributed to the increased expression of PD-L1 on MSCs, expanding in proportion of Th2 and Treg cells [43,44].…”
Section: Immunoregulatory Function Of Mscsmentioning
confidence: 99%
“…However, different types or doses of immunosuppressants may lead to completely different responses. Hajkova et al indicated that the combination of MSCs and immunosuppressive agents not only promoted cell proliferation and Tregs function, but modulated the balance of distinct T-lymphocyte subsets [42]. Inoue et al demonstrated the immunosuppressive effects of MSCs showed in vitro.…”
Section: Influence Of Immunosuppressantmentioning
confidence: 99%